Ground Penetrating Radar Examinations of a Ritual Bathhouse in Ponedel, Lithuania - Fuerstenberg, Madeline M.; Beck, Joseph D.; Schneider, Daniel G.; Kofman, Chloe C.; Jol, Harry M. (My University, 2019)
Based on eyewitness and historical reports, the decimated remains of an old Jewish bathhouse and mikveh, or ritual bath, are believed to be buried in the backyard of a home in Ponedel, Lithuania. Using ground penetrating radar (GPR), we examined the site during the summer of 2018 in order to determine the validity of these claims, map out any potential structures, and determine whether any further archaeological action is justified. During World War II, the Nazis and non-Jewish Lithuanian militiamen murdered about 90 percent of Lithuanian Jews in a span of about three years. Thousands of Jewish cultural structures were destroyed all around the country. Research such as this allows for Lithuanian Jews to reclaim some of their lost history and locate potential locations for memorialization.
Color poster with text, images, maps, photographs, and graphs.
Keywords: Ground penetrating radar (GPR); Holocaust, Jewish (1939-1945)--Lithuania; Ponedel, Lithuania; Posters